2022
DOI: 10.3389/fonc.2022.876664
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Radiomics and Urine Creatinine for the Differentiation of Renal Angiomyolipoma With Minimal Fat From Renal Cell Carcinoma: A Preliminary Study

Abstract: ObjectivesStandard magnetic resonance imaging (MRI) techniques are different to distinguish minimal fat angiomyolipoma (mf-AML) with minimal fat from renal cell carcinoma (RCC). Here we aimed to evaluate the diagnostic performance of MRI-based radiomics in the differentiation of fat-poor AMLs from other renal neoplasms.MethodsA total of 69 patients with solid renal tumors without macroscopic fat and with a pathologic diagnosis of RCC (n=50) or mf-AML (n=19) who underwent conventional MRI and intravoxel incoher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…This approach overcame the problem related to the accurate delineation of tumoral volume of interest (VOI). 52 The same authors provided, in addition, a radiomics CT nomogram for discriminating AML from RCC, 53 built using selected features reaching an AUC, for this nomogram, of 0.968. 54 More recently, Han et al performed a retrospective research in 58 patients with AML and 140 with RCC, pathologically confirmed, to evaluate the prognostic value of CT radiomics in distinguishing AML from RCC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach overcame the problem related to the accurate delineation of tumoral volume of interest (VOI). 52 The same authors provided, in addition, a radiomics CT nomogram for discriminating AML from RCC, 53 built using selected features reaching an AUC, for this nomogram, of 0.968. 54 More recently, Han et al performed a retrospective research in 58 patients with AML and 140 with RCC, pathologically confirmed, to evaluate the prognostic value of CT radiomics in distinguishing AML from RCC.…”
Section: Resultsmentioning
confidence: 99%
“…Razik et al ., 57 performed an MRI analysis to distinguish AML, RCC, and ONC, reporting in an MRI-based radiomics, an AUC > 0.8, with best performing parameter based on the mean of positive pixels (MPP) on DWI (AUC of 0.891). Jian et al 53 instead, evaluated the combined use of MRI radiomics plus urinary creatinine for this purpose in a preliminary study, reporting the best AUC for the T2WI model (0.874), which increased up to 0.919 when combined with urinary creatinine, proposing the addition of other variables to radiomics approach to improve the diagnostic capabilities. Matsumoto et al 58 demonstrated instead that the ADC map was enough in differentiating AML from RCC via a radiomics MRI-based approach, reporting good AUC (0.87) in the validation group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, radiomics models have been developed to best discriminate these lesions. Indeed, in 2022, Jian et al reported for the 1st time a MRI-based radiomics study for differentiation of mf-AML ( n = 19) form RCC ( n = 50) [6 ▪▪ ]. The authors analyzed 396 radiomic features for each MRI sequence, in manually selected region of interest (ROI), in T2WI and intravoxel incoherent motion (IVIM) DWI as well as clinical features.…”
Section: Radiomics and Kidney Massesmentioning
confidence: 99%
“…The study by Jian and colleagues ( 7 ) strived to evaluate the diagnostic performance of magnetic resonance imaging-based radiomics in the differentiation of fat-poor angiomyolipomas from other renal neoplasms. A study conducted on 69 patients allowed the research team to demonstrate how the clinical-radiomics model could represent a valuable noninvasive diagnostic tool to distinguish fat-poor angiomyolipomas from other renal neoplasms.…”
mentioning
confidence: 99%